Metallogenesis of the Lode Gold Deposit in Ilesha Area of Southwestern Nigeria: Inferences from Lead Isotope Systematics (Biological Sciences - PJSIR, 2006)
Studies were carried out on the geochemistry of 18 representative samples of the granite gneiss host rock, common Pb dates on six granite gneiss whole rock samples, six feldspar sample separates, and six samples from the lode gold deposit in the Ilesha schist belt. The AFM plot for the biotite granite gneiss indicated that its protolith was derived from a subduction related tectonic setting. The granite gneiss had low U/Pb and Th/Pb ratios (0.10 to 0.31 and 0.33 to 1.31, respectively), and upper crustal Pb content of 30-47 ppm. The 207Pb/204Pb, 206Pb/204Pb, 208Pb/204Pb, were extremely homogeneous in the host rock, the feldspar, and the pyrite indicating derivation from a subduction related environment like a back arc or island arc. The two-stage Stacy and Kramers (1975) Pb-Pb model dating method of interpretation adopted in this study indicated that the granite gneiss was emplaced at 2750 ± 25 Ma in an orogen. On analysis, common Pb in pyrite yielded an average model age of 550 Ma. This Pb systematics indicated that Au was derived from the volcanics in the Ilesha schist belt by hydrothermal leaching, transported through the same medium and deposited in the massive quartz veins as thio-complexes from which native gold was liberated through interaction of the ore fluid and spinnels in the host rock.